DEVELOPING LEARNING MODEL OF ENVIRONMENTAL EDUCATION COURSE BASED ON ETHNO STEM FOR PRESERVICE TEACHERS TO ENHANCE SUSTAINABILITY LITERACY - Oktian Fajar Nugroho, - (2022)
Indonesia, as a large nation have abundant human resources and local wisdom should be a play a great role in the development of science and technology. Integrating Indonesia local wisdom and STEM Education can be used by utilizing the principles of STEM based on local wisdom. This study aims to develop and validate a learning model that can improve the sustainability literacy of students by emphasizing Indonesian local wisdom. This study found a new model namely Ethno-STEM Learning Model, it was developed, validated, and implemented to enhance preservice teachers' sustainability literacy. Four sustainability literacy aspects were used there are conceptual awareness, identity development, skill development, and developing confidence. The main characteristics of Ethno-STEM are defining local-wisdom problem/local wisdom products design challenge, build possible solution to solve local wisdom problem/products design challenge, constructing functioning product of local wisdom, testing the prototypes of local wisdom products, and redesign the prototypes of local wisdom products and communicate the solution of local-wisdom problem. Design and Development Research was implemented in this study. The subjects in this study consist of 47 pre-service teachers of elementary education department who are taking environmental education courses at Esa Unggul University in Jakarta. Three themes of worksheet based on Ethno-STEM Learning Model were used in this study are eco-friendly boat, drying fish machine, and water purifying system. Those three themes were implemented in lectures for 1 semester in 14 meetings x 3 credits and 2 meetings for exams (middle and final exam). The projects were carried out in groups, each group carried out 3 projects starting from an eco-friendly boat, drying fish machine, and water purifying system. A set of sustainability literacy test were developed, validated and implemented. The results of this study Ethno-STEM Learning Model have been revised and validated by the experts and practitioners. Ethno-STEM Learning Model indicated there was significant improvement in sustainability literacy test after given Ethno-STEM learning model respectively.